Rancang Bangun Sistem Komunikasi antar UAV untuk Formasi UAV - Rendra Dwi Firmansyah; Esa Apriaskar; Tika Erna Putri (Departemen Teknik Elektro dan Informatika Sekolah Vokasi UGM, 2020)
UAV formation is one of techology development in UAV world. The UAV formation can be utilized in various fields including agriculture, mapping and defense security (HANKAM). Communication is one of the important components in making UAV formations. To make UAV formations, position and direction data (AHRS) from each UAV will be sent to other UAVs so that when forming UAV formation, no collisions occur between UAVs. This study uses a star topology like the one on a computer network. This method involves two or more UAVs, both of which will exchange data. In this study the data sent is in the form of a dummy data package using the xbee module. The purpose of this study is the initial model of communication between UAVs which can later be developed into more complex communication models for many UAVs. The results obtained in the form of maximum communication distance between UAVs is 50m and the recommended optimal distance is 10-20m.